2006
DOI: 10.1590/s0100-204x2006000700014
|View full text |Cite
|
Sign up to set email alerts
|

Digestibilidad in situ de dietas con harina de nopal deshidratado conteniendo un preparado de enzimas fibrolíticas exógenas

Abstract: Se evaluó el efecto de un preparado de enzimas fibrolíticas exógenas (celulasas y xilanasas) en la degradabilidad in situ de la materia seca (DisMS), fibra detergente neutro (DFDNr) y fibra detergente ácido residual (DFDAr), en dietas altas o bajas en harina de nopal deshidratado. Se aplicaron concentraciones de 0, 1, 2 y 3 g de enzima por kilogramo de materia seca al inicio y 24 horas antes de la degradación in situ. Se determinó la concentración de ácidos grasos volátiles totales y de nitrógeno amoniacal a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
(5 reference statements)
0
2
0
1
Order By: Relevance
“…However, these values are lower than those published by Medina-Romo et al . [ 36 ], who reported 871 g/kg DMDis in a cattle diet containing 20% corn stover, 20% alfalfa hay, 26.7% commercial concentrate (18% CP), and 33.3% cactus meal. The discrepancies between this study and those reported by the aforementioned authors are related to the composition and efficiency of the rumen microbiota present in the cattle used for the in situ test [ 37 ] and the feed offered during the test [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these values are lower than those published by Medina-Romo et al . [ 36 ], who reported 871 g/kg DMDis in a cattle diet containing 20% corn stover, 20% alfalfa hay, 26.7% commercial concentrate (18% CP), and 33.3% cactus meal. The discrepancies between this study and those reported by the aforementioned authors are related to the composition and efficiency of the rumen microbiota present in the cattle used for the in situ test [ 37 ] and the feed offered during the test [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancies between this study and those reported by the aforementioned authors are related to the composition and efficiency of the rumen microbiota present in the cattle used for the in situ test [ 37 ] and the feed offered during the test [ 35 ]. This is because in our study, the diet was based on 50% mango silage and 50% commercial feed (12% CP), and the previous studies [ 36 , 38 ] used to compare results fed the cattle with the same diet they evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Este grande problema da pecuária do Nordeste brasileiro, que é a oferta irregular de forragem, causa um grande prejuízo a este segmento da economia. A constância no aparecimento de anos secos faz da palma forrageira um alimento classificado como estratégico para esses períodos, quando o crescimento de outras forrageiras é limitado pelo baixo índice pluviométrico (CAVALCANTE, 2007;ROMO et al, 2006).…”
Section: Importância Para O Semiárido Brasileirounclassified